Visualisasi Algoritma sebagai Sarana Pembelajaran K-Means Clustering - Alethea Suryadibrata; Julio Christian Young (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Algorithm Visualization (AV) is often used in computer science to represents how an algorithm works. Educators believe that visualization can help students to learn difficult algorithms. In this paper, we put our interest in visualizing one of Machine Learning (ML) algorithms. ML algorithms are used in various fields. Some of the algorithms are used to classify, predict, or cluster data. Unfortunately, many students find that ML algorithms are hard to learn since some of these algorithms include complicated mathematical equations. We hope this research can help computer science students to understand K-Means Clustering in an easier way.